Computing and Combinatorics c - Kim, Donghyun; Uma, R. N.; Cai, Zhipeng; Lee, Dong Hoon.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This book constitutes the proceedings of the 26th International Conference on Computing and Combinatorics, COCOON 2020, held in Atlanta, GA, USA, in August 2020. Due to the COVID-19 pandemic COCOON 2020 was organized as a fully online conference. The 54 papers presented in this volume were carefully reviewed and selected from 126 submissions. The papers cover various topics, including algorithm design, approximation algorithm, graph theory, complexity theory, problem solving, optimization, computational biology, computational learning, communication network, logic, and game theory.
Subspace approximation with outliers -- Linear-time Algorithms for Eliminating Claws in Graphs -- A new lower bound for the eternal vertex cover number of graphs -- Bounded-Degree Spanners in the Presence of Polygonal Obstacles -- End-Vertices of AT-free Bigraphs -- Approaching Optimal Duplicate Detection in a Sliding Window -- Computational Complexity Characterization of Protecting Elections from Bribery -- Coding with Noiseless Feedback over the Z-channel -- Path-monotonic Upward Drawings of Plane Graphs -- Seamless Interpolation between Contraction Hierarchies and Hub Labels for fast and space-e cient Shortest Path Queries in Road Networks -- Visibility polygon queries among dynamic polygonal obstacles in plane -- How Hard is Completeness Reasoning for Conjunctive Queries? -- Imbalance Parameterized by Twin Cover Revisited -- Local Routing in a Tree Metric 1-Spanner -- Deep Specification Mining with Attention -- Constructing Independent Spanning Trees in Alternating Group Networks -- W[1]-Hardness of the k-Center Problem Parameterized by the Skeleton Dimension -- An Optimal Lower Bound for Hierarchical Universal Solutions for TSP on the Plane -- Quantum Speedup for the Minimum Steiner Tree Problem -- Access Structure Hiding Secret Sharing from Novel Set Systems and Vector Families -- Approximation algorithms for car-sharing problems -- Realization Problems on Reachability Sequences -- Power of Decision Trees with Monotone Queries -- Computing a maximum clique in geometric superclasses of disk graphs -- Visibility -- Tight approximation for the minimum bottleneck generalized matching problem -- Graph Classes and Approximability of the Happy Set Problem -- A Simple Primal-Dual Approximation Algorithm for 2-Edge-Connected Spanning Subgraphs -- Uniqueness of $DP$-Nash Subgraphs and $D$-sets -- On the Enumeration of Minimal Non-Pairwise Compatibility Graphs -- Constructing Tree Decompositions of Graphs with Bounded Gonality -- Election Control through Social In uence with Unknown Preferences -- New Symmetry-less ILP Formulation for the Classical One Dimensional Bin-Packing Problem -- On the Area Requirements of Planar Greedy Drawings of Triconnected Planar Graphs -- On the Restricted 1-Steiner Tree Problem -- Computational Complexity of Synchronization under Regular Commutative Constraints -- Approximation algorithms for general cluster routing problem -- Hardness of Sparse Sets and Minimal Circuit Size Problem -- Succinct Monotone Circuit Certi cation: Planarity and Parameterized Complexity -- On Measures of Space Over Real and Complex Numbers -- Parallelized maximization of nonsubmodular function subject to a cardinality constraint -- An improved Bregman $k$-means++ algorithm via local search -- On the Complexity of Directed Intersection Representation of DAGs -- On the Mystery of Negations in Circuits : Structure vs Power -- Even better xed-parameter algorithms for bicluster editing -- Approximate Set Union via Approximate Randomization -- A Non-Extendibility Certi cate for Submodularity and Applications -- Parameterized Complexity of Maximum Edge Colorable Subgraph -- Approximation Algorithms for the Lower-Bounded k-Median and Ist Generalizations -- A Survey for Conditional Diagnosability of Alternating Group Networks -- Fixed Parameter Tractability of Graph Deletion Problems over Data Streams -- Mixing of Markov Chains for Independent Sets on Chordal Graphs with Bounded Separators.
Keywords: Computers; Computer organization; Data structures (Computer science).; Artificial intelligence; Theory of Computation; Computer Systems Organization and Communication Networks; Data Structures and Information Theory; Information Systems and Communication Service; Artificial Intelligence